Strategies of Elementary School Teacher Education Students in Overcoming Public Speaking Anxiety During Academic Presentation Activities - Siti Nova Chusnul Khotimah; Ifa Seftia Rakhma Widiyanti (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Academic presentations are part of the pedagogical training of Elementary School Teacher Education (PGSD) students, and many of them experience anxiety about public speaking. This research was an attempt to see how anxiety manifests in the lives of public speakers, how they cope with it, and what factors determine if coping strategies work. The approach used was qualitative descriptive method, number of respondents of PGSD students in the selection of 5 students used purposive sampling at PGRI Ronggolawe University. Semi-structured in-depth interviews and field notes were used to collect data and subsequently analyzed thematically using the Self-Efficacy theory. The results indicate that students are anxious in 3 aspects: the physiological aspect, such as trembling, sweating and fast heartbeat, the cognitive aspect, fear of negative evaluation and difficulty in concentrating, and the behavioral aspect, avoiding eye contact, and speaking too fast. Students employed both problem-focused and emotion-focused coping strategies to manage these situations. Problem-focused approaches included thorough preparation and repeated practice, while emotion-focused coping involved relaxation exercises, breathing techniques, visualization, positive self-talk, and seeking social support. Self-efficacy, previous experience, quality of preparation and support from peers or lecturers are all significant factors in the effectiveness of the strategies. In general, public speaking anxiety could be dealt with by adaptive coping strategies and supportive learning environments to boost students' abilities to communicate.